STUDENTSâ BASIC PROBLEMS IN LEARNING ENGLISH: MASTERING VOCABULARY AND GRAMMAR - Agustina, Dwi (Vidya Karya Jurnal Kependidikan, 2013)
learning English for Indonesian students is the necessity since they have been in elementery school to higher education. However, many students consider English difficult although they have been learnt English for years. Such condition motivates the writer to research the problem the students have. The writer believes that comprehending the studentsâ problem in learning English help them to teach in a better manner because the writer has known to solve the studentsâ problem.